Perancangan Interior Pusat Informasi Dan Pelatihan Wushu Di Surabaya - Yusak Yuwono; Andereas Pandu Setiawan (Intra, 2014)
Indonesia has a lot of history and culture which we should keep them well, so they will not be destroyed as time passes. One of them is martial art Wushu, which long known in Indonesia in the name of ‘Kunthauw’. This martial art which came from China has live side by side with the life of Indonesian’s society for a long time, but it’s a pity that this martial art practitioner mostly still stand just by themself. Society itself often has some misunderstanding about Wushu. Interior designers play their parts to create a place which combine Wushu practitioners and giving enough information for Indonesian people about Wushu.